Peningkatan kemampuan analisis gaya dan gerak melalui model guided inquiry - Peni Astuti; Sandra Bayu Kurniawan; Siti Istiyati (Didaktika Dwija Indria, 2019)
This research aims to improve the force and movement analysis capabilities of fourth grade students of the Elementary School Pengungkulan in the academic year 2018/2019. This Classroom Action Research (CAR) is held in two cycles. Each cycle consists of two meetings with various stages in each meeting namely, planning, implementation, observation, and reflection. As a research object is the fourth grade students of Elementary School Penungkulan who are 30 students. The data collection techniques in this research are tests and non-tests. The data validation used is content validation. Data analysis using descriptive qualitative method of Miles-Huberman consisting of data reduction, data presentation, and conclusion. The completeness results of the ability to analyze of the students in action research is 20%  in classical. In the first cycle of the first meeting, the percentage of completeness was 43.4% in classical, while in the second meeting, the completeness was 60% in a classical. The second cycle as a continuation of the first cycle, the percentage of completeness at the first meeting was 76.3% in classical and at the meeting 2 the percentage of classical completeness was 83%Keywords: guided inquiry, analysis, force and movement, elementary school